A-Technologies: Challenges in SMEs Technology Company - Fakhrul Anwar, Zainol; Nalini, Arumugam; Nor Asmahani, Ibrahim; Wan Norhayate, Wan Daud (2014)
A-Technologies (A-Tech) is one of the established small medium enterprises (SMEs) owned by husband and wife, which operated since 1998 in Kuala Terengganu, Terengganu, Malaysia. The company’s core business is producing and distributing fiberglass tanks, the Fiber Reinforced Plastic (FRP) tank and the High Density Polyethylene (HDPE) tank. A-Tech has well-experienced workers who worked almost 10 years at the company that contributed to the success of the company’s establishement. A-Tech also has a good business network and contacts especially with those in the semiconductor industry. These networks also had helped the company during the start-up stage until gaining its position in the market. A-Tech business potential depended on their product’s performance as the new technology added-up a better performance of its products. However, like any other business venture, A-Tech also facing several issues and operational challenges. This case study will look at the management and operational challenges and issues faced by ATech.